1991
DOI: 10.1177/001316449105100411
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Personal Dimensions of Prospective Teachers' Reflective Abilities

Abstract: With an increasing concern that teachers develop reflective thinking abilities as part of their teacher training programs, there comes a need to know more about the reflector. This knowledge can guide teacher education programs in providing experiences that will enhance or encourage reflective ability. A Q-technique factor analysis was employed to examine a number of psychological and personal characteristics of prospective teachers in order to provide a description of those who have been classified as reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Gipe, Richards, Levitov, and Speaker concluded that the ability to reflect is an important ability for a (case) teacher. They thus followed an argument by Charvoz, Crow, and Knowles, who stated that the development of self-reflective attitudes is a specific aim of inquiry-oriented teacher education programs (1988( , in: Gipe et al 1991. Gipe et al differentiated a reflective prospective teacher from a non-reflective one (1991,916) and tried to divide these groups by analyzing "… certain psychological and personal characteristics of prospective teachers …" (ibid., 916).…”
Section: Introductionmentioning
confidence: 99%
“…Gipe, Richards, Levitov, and Speaker concluded that the ability to reflect is an important ability for a (case) teacher. They thus followed an argument by Charvoz, Crow, and Knowles, who stated that the development of self-reflective attitudes is a specific aim of inquiry-oriented teacher education programs (1988( , in: Gipe et al 1991. Gipe et al differentiated a reflective prospective teacher from a non-reflective one (1991,916) and tried to divide these groups by analyzing "… certain psychological and personal characteristics of prospective teachers …" (ibid., 916).…”
Section: Introductionmentioning
confidence: 99%
“…Reflective ability is the capacity to question and critically analyse experience (Gipe et al 2001). King and Kitchener (2001) outline three stages in reflective ability: prereflective (limited to concrete black and white concepts), quasi reflective (in which uncertainty is recognised as a problem) and reflective thinking (in which uncertainty and complexity are integrated into a justifiable opinion for a judgement to be formed).…”
Section: Introductionmentioning
confidence: 99%